Prevalence and identification of oral candida species in patients with type 2 diabetes in Yogyakarta - Agustina, Dewi; Chrisnawati, Regina Titi; Chrismawaty, Bernadetta Esti; Wongsohardjono, Sri Budiarti; Naritasari, Fimma; Sarasati, Andari (Majalah Kedokteran Gigi Indonesia, 2023)
Patients with diabetes are prone to recurring and even resistant Candidiasis, making treatment challenging. Many hypotheses proposed related to susceptibility of diabetic patients to Candida. The prevalence and species of Candida in a particular diabetic community might be different compared to other diabetic community. This study aimed to determine the prevalence of Candida colony and its species in the oral cavity of diabetic patients included in the CDM (Chronic Disease Management) program in Yogyakarta. One hundred patients with type 2 diabetes (n= 100) were recruited as the subjects of this study. The subjects were classified into controlled and uncontrolled Diabetes mellitus (DM). Samples of oral rinse solution were collected to determine the species of Candida and number of Candida colonies using CHROMagar Candida medium. There were 47 and 53 of subjects with controlled and uncontrolled DM, respectively. The mean number of Candida colony in the subjects with controlled diabetes (1003.13) was higher than that in the subjects with uncontrolled diabetes (478.43). The Candida colony most commonly identified in the subjects with controlled and uncontrolled diabetes were C. albicans and C. glabrata, respectively. Female patients had higher mean number of Candida colony (859.51) compared to male (299.21). The Candida colony most often identified in both genders was C. albicans. In addition, the subjects of this study consisted of 83 geriatric subjects and 17 non geriatric subjects, in which the mean number of Candida colony in the geriatric subjects (761.77) was higher than that in the non-geriatric subjects (545.71). The Candida colony most often identified in the geriatric subjects and non-geriatric subjects was C. albicans and C. glabrata, respectively. The Mann Whitney test demonstrated that there was a significant difference (p = 0.009) of the mean number of Candida colony between male and female. However, there was no significant difference of the mean number of Candida colony between ages (p = 0.060) and diabetic status (p=0.175). It can be concluded that the Candida species most commonly identified in all the subjects was Candida albicans with the mean colony number of 349.96, followed by C. glabrata (225.97), C. krusei (144.91), C. tropicalis (3.67), and other species (2.02).